External Treatment With Chinese Herbal Medicine for Chemotherapy-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis - Li, Quan-yao; Cai, Fei-hong; Lu, Ying; Liu, Hui; Wang, Xiao; Li, Fan-lian; Shi, Jun (Frontiers in Pharmacology, 2022)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse reaction of chemotherapy. Many studies have confirmed that Chinese medicine has unique advantages in treating CIPN. However, there is no standard prescription of traditional Chinese medicine in clinical practice, as well as objective outcome index and similar efficacy. Therefore, in this study, a systematic review of randomized controlled trials (RCTs) was performed to evaluate the clinical efficacy on external treatment of Chinese herbal medicine (CHM) for the treatment of chemotherapy-induced peripheral neuropathy, so as to provide evidence-based medical evidence on CHM external treatment for CIPN. Methods: The literatures on relevant clinical RCTs assessing CHM external treatment of chemotherapy-induced peripheral neuropathy were searched in 9 electronic databases including China National Knowledge Infrastructure Database (CNKI), China Biology Medicine disc (CBM), China Science and Technology Journal Database (VIP), Wanfang Database (WANFANG), PubMed, Cochrane Library, MEDLINE, Web of Science and OVID from inception up to July, 2021. Meta-analysis was performed on these literatures using ReVman5.3 software. Results: 1354 relevant literatures were screened out. According to the inclusion and exclusion criteria, 33 clinical studies were included finally. There are 2356 patients in total, including 1208 in the treatment group and 1148 in the control group. In the treatment group, peripheral neurotoxicity rate, total effective rate, KPS score, TCM syndrome score and efficacy, pain NRS score and pain relief rate were improved more than those in the control group, and the difference was statistically significant (P＜0.01). Meanwhile, the improvement of peroneal and median nerve conduction velocity was also better than that of the control group, and the difference was statistically significant(P＜0.05). By making funnel plot for the incidence of peripheral neurotoxicity and the total effective rate, it could be found that the left and right sides were basically symmetrical and the publication bias was low. Conclusion: CHM external treatment was an effective method for treating chemotherapy-induced peripheral neuropathy, which could significantly improve the clinical symptoms and the quality of CIPN patients’ life.